Astronomical Seeing Measurement of two Observatory Sites in Malaysia: The DIMM Method - Zainuddin, Mohd Zambri; Abd Aziz, Noradni Azman; Arif, Adibah; Ahmad, Nazhatulshima; Haron, Saedah (Malaysian Journal of Science, 2006)
A low cost differential image motion monitor (DIMM), consisting of a 12-inch Meade, an STV Santa Barbara Instrument Group (SBIG) auto guiding CCD camera and a notebook is described. The system was used for seeing measurements in Kuala Lumpur on August 2002 and January 2003, also in Merang, Trengganu on March 2003. The preliminary results of these measurement show that the seeing value in Kuala Lumpur is greater than 2 arcseconds. Seeing value in Merang is about 1 arcsecond. Merang however, has better seeing than Kuala Lumpur. Kuala Lumpur has slightly worse seeing (>3 arcseconds) compared to Merang.